On Architecture Design, Congestion Notification, TCP Incast and Power Consumption in Data Centers - Yan Zhang; Ansari, N. (IEEE Communications surveys and tutorials, 2013)
With rapid deployment of modern data center networks (DCNs), many problems with respect to DCN architecture, congestion notification, TCP Incast, and power consumption have been observed. In this paper, we provide a comprehensive survey of the most recent research activities in DCNs, with emphasis on the network architecture design, congestion notification algorithms, TCP Incast, and power consumption. We describe in detail the architecture of a typical modern DCN. Furthermore, we investigate the challenges of the typical tree-based hierarchical DCN architecture encountered today and the requirements for the optimal DCN architecture, and we classify the proposed DCN architectures into switch-centric topology and server-centric topology. A section is also devoted to describe some newly proposed DCN architectures. We present a brief overview of the TCP Incast problem along with previously proposed solutions. We also review the recent energy-efficient solutions to minimize the power consumption in DCNs. Finally, we outline possible future research topics in DCNs.